2021
DOI: 10.21462/jeltl.v6i3.629
|View full text |Cite
|
Sign up to set email alerts
|

Functional Patterns of Lexical Bundles and Limitations in Academic Writing by Thai L2 English Learners

Abstract: <p><em>Lexical bundles, which serve as markers of fluent and appropriate language use, are referred to as "building blocks of discourse" because they occur frequently in written texts and help readers and writers process information more quickly. They also provide important linguistic functions. However, lexical bundles can vary across genres, domains and even sections of the same work, which can be challenging for novice and non-native writers. The purposes of this study are to explore how Thai L2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…Corpus linguistics studies have found that in natural language there is a high-frequency, fixed form, meaning stable language structure, which is now referred to as the "block" [1,2]. Blocks contain grammar, semantics, and context and is the ideal language unit.…”
Section: Introductionmentioning
confidence: 99%
“…Corpus linguistics studies have found that in natural language there is a high-frequency, fixed form, meaning stable language structure, which is now referred to as the "block" [1,2]. Blocks contain grammar, semantics, and context and is the ideal language unit.…”
Section: Introductionmentioning
confidence: 99%
“…He compiled a massive bundle of 2390093 words where he found that there is a huge number of changes in the usage of these bundles throughout these 20 years. Khamkhien (2021) in his analysis of Thai L2 English learner's academic writing, found a difference in the use of native and non-native writers when it comes to lexical bundles. This study was done on 53 research reports containing 60 thousand-plus words.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Academic writing is one of the formal writing styles used in schools and colleges. Due to its formality, the writer requires carefulness to write complete sentences and organize them specifically (Ariyanti, 2016;Khamkhien, 2021;Therova, 2021). The writer also needs to answer and demonstrate an understanding of the subject discussed in academic writing.…”
Section: Introductionmentioning
confidence: 99%